Evidências da influência dos tipos psicológicos no comportamento dos tomadores de decisões financeiras - Alberto, Gabriel Santos (2014)
The aim of this study was to investigate the relationship between the theory of psychological types and the decision-making, focusing on behavioral biases, anchoring, overconfidence, representativeness, mental accounting and loss aversion. A questionnaire was developed and 319 valid responses were obtained. We used descriptive statistics, parametric and nonparametric tests, and structural equation modeling, using IBM SPSS Statistics and AMOS. The results show that decision-making is influenced by the dimension extraversion-introversion, sensation-intuition, thinking-feeling, judgment-perception, gender, education, income and age. The extraversion-introversion dimension influence on the anchoring and loss aversion bias, sensation-intuition on the representativeness bias; thinking-feeling on the overconfidence, representativeness and loss aversion bias; judgment-perception on the overconfidence, representativeness, mental accounting and loss aversion bias; gender on the anchoring, overconfidence, representativeness, mental accounting and loss aversion bias; education on the overconfidence, representativeness and loss aversion bias; income on the anchoring, overconfidence, representativeness, mental accounting and loss aversion bias, and age on the anchoring, overconfidence, representativeness and mental accounting bias. This work contributes adding new evidence that behavior of decision makers is influenced by psychological types and therefore bias is possible to be mitigated